DEVELOPMENT OF A SYSTEM FOR AUTOMATIC TEMPERATURE CONTROL OF THE HEATING SURFACES OF THE APPARATUS FOR CONDUCTIVE DRYING OF MEAT - SKRYPNYK, VIACHESLAV; BYCHKOV, YAROSLAV; MOLCHANOVA, NATALYIA; PONOMARENKO, BOGDAN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents the results of the development of a system for automatic temperature control of the heating surfaces of the apparatus for conductive drying of meat. The development of an experimental stand for conducting a number of studies to determine the optimal parameters of the conductive drying process, in particular the temperature of the heating surfaces, the duration of drying, and others, has been substantiated. The technical capabilities have been considered and discrepancies in the basic configuration of the conductive meat drying device based on the double-sided grill "Frosty SP-1A3" for using in the experimental stand have been empirically identified. It has been established that the temperature of the upper and lower heating surfaces differs from the specified one to varying degrees, but such a deviation value is unacceptable. The need to improve the automatic temperature control system of the experimental stand for conductive meat drying has been determined. The composition of automation elements has been defined and the main requirements for the automatic temperature control system of heating surfaces have been determined. The advantages of using Proportional-Integral-Derivative (PID) temperature control in inertial systems have been considered. The tasks of developing an electrical circuit diagram and its elements composition to ensure the operation of the automatic temperature control system have been solved. The design modification of the double-sided grill "Frosty SP-1A3" was carried out by installing two Pt100 temperature sensors in the heating surface. A two-stage adaptation and adjustment of the PID coefficients of the "TRC-02 Universal Plus" thermostat was performed. To increase the reliability of the results obtained, the RS-485 interface was used for communication with a computer using the "Prompribor" software. Based on the results of the conducted research, a system for automatic regulation of the temperature of heating surfaces using PID control has been developed; characterized by sufficient speed and reliability it ensures the efficient operation of the apparatus for conductive drying of meat as part of the experimental stand.